Mathematics Learning Activities Of Students Of SMP Negeri 5 Tondano In The Transitional/Post Pandemi Covid-19 Period - Grifiany Meisy Pongayow; Victor R. Sulangi; Cori Pitoy (Departement of Mathematics Education, 2023)
This study aims to describe mathematics learning activities during the co-19 pandemic and after the co-19 pandemic at SMP N 5 Tondano. Approximately 2 years of the brave learning process was carried out, which might make students experience problems in terms of ethics or attitude because while learning, the brave teacher also lacks in supervising students' attitudes and behaviour, so with this change in learning, the difference is very visible. This research is qualitative descriptive research. Data was collected using observation techniques, interviews, and documentation. The results showed that students' mathematics learning activities during the transition/post-covid-19 pandemic were going well at school following the schedule of learning activities the school had prepared. However, students' mathematics lessons are less effective in the process. This is evidenced by observational data, which shows: 1) Teachers are less creative using various learning models, 2) Students do not respond to learning, 3) Students lack interest in mathematics, 4) Students are not actively involved in learning, and 5) Courageous learning that takes so long results in students being very dependent on the internet network. This resulted in the teacher experiencing several obstacles in the students' mathematics learning activities attractively. It can be interpreted that students' mathematics learning activities at SMP N 5 Tondano during the transition/post-covid-19 pandemic were less effective due to courageous learning activities.